Evaluation of genetic and phenotypic parameters growth traits in organized flock of Chokla sheep of Rajasthan - PRAKASH, PRAKASH; YADAV, S B S; PATEL, A K; NARULA, H K; CHOPRA, ASHISH (The Indian Journal of Animal Sciences, 2019)
The sire effect was highly significant (P≤0.01) on all growth traits.The sex effect of lamb was highly significant (P≤0.01) on all growth traits but non-significant on 12 months body weight, period effect was highly significant (P≤ 0.01) on all growth traits but non-significant on birth weight. The effect of dam’s age was highly significant (P≤0.01) on birth weight, 3 months weight, ADG3 and nonsignificant effect for 6, 9, 12 months body weights, ADG1 and ADG2. The effect of season of birth was highly significant (P≤ 0.01) on all growth traits but non-significant effect for 12 months body weights. The effect of dam’s weight as a covariate was highly significant (P≤0.01) on birth, 3, 6, 9 months body weights and ADG1 and significant (P≤0.05) on 12 months body weights and non-significant for ADG2 and ADG3. The heritability estimates from WOMBAT (animal model 1) method for body weights and average daily gains were low to medium. Estimates of genetic correlations between body weights with weights at subsequent ages were positive and ranged from 0.065 to 0.885, and average daily gains during different phase ranged from –0.088 to 0.322. Estimates for phenotypic correlations between body weights with weights at subsequent ages ranged from 0.255 to 0.818, and average daily gains during different phase ranged from –0.22 to 0.141.